ETHICS OF GOLD INTALLMENT PLANS IN PAKISTANI SHARIA BANKS: PERSPECTIVE OF A SHARIA ECONOMIC LAW - Ullah Khan, Sami (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2024)
Pakistan is the country with the largest Muslim population in the world, with a total population of 220 million, of which around 96% are Muslims. Islam plays a central role in social, cultural, and political life in Pakistan, a country with a rich Islamic heritage and cultural diversity. In global economic development, various demands have emerged to adapt to changing social and economic conditions increasingly diverse by society's needs. This significantly impacts the banking sector, which must innovate to remain competitive. In Pakistan, both conventional commercial banks and Islamic banks face similar challenges. Islamic banking, in particular, aims to meet the needs of Sharia-based financial transactions, considering that the majority of Pakistan's population is Muslim. One of the innovative products offered by Islamic banks is gold installments. This research uses qualitative methods to analyze gold installment products from the perspective of Sharia economic law and ethics. The aim is to identify the service mechanism for this product, ensure its conformity with the provisions of Islamic Sharia economic law and the fatwas of the Shariah Advisory Boards of Pakistan, and assess its benefits in terms of economic ethics. The research results show that the service mechanism for gold installment products with murabahah contracts at Sharia banks does not violate Sharia economic law and is by the provisions of the Pakistani Shariah Advisory Boards. This product is popular with the public because it makes it easier for them to buy gold in installments, considering that gold is an asset whose value tends to increase.